Physical Properties of Polyacrylamide/Polyvinylalcohol Silica Nanocomposites - E. Abulyazied, Dalia; A. Mansour, Nahla; M. Mazrouaa, Azza; G. Mohamed, Manal (Journal of Research Updates in Polymer Science, 2016)
In this paper, samples of Polyacrylamide (PAAm) nanosilica nanocomposites were prepared having different concentration of nanosilica (0.125, 0.25, and 0.5). Polyacrylamide (PAAm) and poly (vinyl alcohol) (PVA) were blended with different ratio (3/1, 1/1, 1/3) using solution-cast technique. The prepared films were characterized by Fourier transform infrared (FTIR), X-ray diffractions (XRD) and scanning electron microscopy (SEM). FTIR spectra showed the presence of hydrogen bonding between–CONH2 groups in PAAm and –OH group in PVA and confirm the hydrophilic nature of the blends. X-ray diffractions shows the presence of a strong broad peak centered at 22º (2θ) confirms the amorphous nature of silica which is supposed to be the characteristic of SiO2. The results obtained from different experimental techniques were supported by SEM image analysis. The thermal stability of the nanocomposites enhanced by increasing the silica content in the blend. The DC electrical conductivity was studied for all prepared samples. It was found that the conductivity increase by increasing silica content as well as, increased by increasing the wt% of PVA.